Direct Measurement of Plant Cellulose Microfibril and Bundles in Native Cell Walls - Song, Bo; Zhao, Shuai; Shen, Wei; Collings, Cynthia; Ding, Shi-You (Frontiers in Plant Science, 2020)
Plants use rigid cellulose together with non-cellulosic matrix polymers to build cell walls. Cellulose microfibrils comprises linear β(1,4)-glucan chains packed through inter- and intra-chain hydrogen-bonding networks and van der Waals forces. Due to its small size, the number of glucan chains and their arrangement in a microfibril remains elusive. Here we used atomic force microscopy (AFM) to directly image fresh tissues of maize (Zea mays), and different primary cell walls (PCWs) and secondary cell walls (SCWs) were analyzed under near-native conditions. We observed large micrifibril bundles in the PCWs, which split into small bundles or individuals. In the SCWs predominantly twinned or individual microfibrils appeared to be nearly-parallel, well-separated and embedded in the matrix polymers without splitting effect. By exploring cellulose structure in different types of cell walls, we were able to measure the individual microfibrils in elongated PCWs at the sub-nanometer scale. The dimension of a microfibril was measured at 3.68 ± 0.13 nm in width and 2.25 ± 0.10 nm in height. By superimposing multiple AFM height profiles of these individual microfibrils, the overlay area representing the cross-section was estimated at 5.6±0.4 nm2, which fitted well to an 18-chain model packed as six sheets with 234432 conformation. This study provides the most accurate measurement of the fundamental structure of plant cellulose microfibril. Our findings also suggest that multiple microfibrils are synthesized as large bundles in PCWs and splitting to allow cell expanding and elongating, while in SCW cell growth has ceased only individual or twinned microfibrils are deposited, indicating different mechanisms of cellulose biosynthesis in PCW and SCW.